Determinan Kepuasan Wajib Pajak UMKM Terhadap Penggunaan Jasa Konsultan Pajak - Hardi Juliawan; Dekar Urumsah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine the influence of reliability, responsiveness, guarantee, empathy, physical evidence, flexibility and price factors on satisfaction with tax consultant services. This research uses a quantitative approach with survey methods and questionnaire techniques distributed to MSME taxpayers in Indonesia who have used tax consultants. Data were collected using convenience sampling techniques, the sample obtained was 330 respondents who were analyzed using SEM-PLS with SmartPLS 3. Based on hypothesis testing, the research results showed that reliability, responsiveness, guarantee, empathy, physical evidence, flexibility and price had a positive and significant effect on satisfaction with tax consultant services. This research uniquely combines both the SERVQUAL model framework and the marketing mix to evaluate and provide a comprehensive analysis of the dimensions of service quality and marketing strategies on MSME taxpayer satisfaction in using tax consultants.